Clinical Presentation and Differentiation Between Behavioral Problems and Psychosis in Individuals with Intellectual Developmental Disorder: A Narrative Review - Archana Mohan Vijayalakshmi; Kothyala Bala Ravikumar (Journal of Psychiatry and Psychological Sciences, 2026)
Intellectual Developmental Disorder (IDD) is a neurodevelopmental disorder characterized by significant limitations in intellectual functioning and adaptive behaviour that originate during the developmental period [1,2]. Individuals with IDD are at increased risk of psychiatric comorbidities, particularly behavioral disturbances and psychotic disorders [3-5]. Distinguishing behavioral problems intrinsic to IDD from psychosis remains one of the greatest diagnostic challenges in psychiatric practice because communication deficits, cognitive impairment, and diagnostic overshadowing often obscure the clinical picture [4,5,6]. Misdiagnosis may result in unnecessary exposure to antipsychotic medications or delayed treatment of genuine psychotic illness [5,7]. This narrative review summarises the current literature about the epidemiology, clinical presentation, neurobiological mechanisms, neuropsychological characteristics, assessment, differential diagnosis, and management of behavioral problems and psychosis in individuals with IDD. A comprehensive literature search was conducted using PubMed, Google Scholar, Scopus, and WHO resources, focusing on studies published in English. Existing evidence indicates that behavioral disturbances are usually precipitated by environmental stressors, communication difficulties, sensory dysregulation, or learned maladaptive responses, whereas psychotic disorders are characterized by disturbances in perception, thought content, and reality testing with a noticeable decline from baseline functioning. Diagnostic overshadowing remains a significant barrier to early identification of psychiatric disorders in this population [5,7]. Structured clinical assessment, detailed caregiver interviews, longitudinal evaluation, and multidisciplinary management are essential for accurate diagnosis and appropriate intervention. Further research from low- and middle-income countries, particularly India, is required to improve culturally relevant assessment tools and strengthen evidence-based clinical practice. Background Intellectual Developmental Disorder (IDD) affects approximately 1–3% of the global population and represents one of the most common neurodevelopmental disorders [1,3,8]. Improvements in neonatal care and survival have increased the number of individuals with IDD reaching adulthood, making psychiatric comorbidity an increasingly important public health concern [7]. Behavioural disturbances and psychotic disorders contribute substantially to caregiver burden, reduced quality of life, institutionalization, and healthcare utilization [3,4,7]. Accurate differentiation between these conditions remains essential for effective management and prevention of inappropriate pharmacological treatment [5,7].